#MeToo and the witching hour: contemporary feminist discourse on the representation of witchcraft in The Chilling Adventures of Sabrina - Steinke, Danielle (My University, 2019)
The witch has become an all-encompassing metaphor for a wide range of theoretical perspectives and interpretations. In this thesis, I want to emphasize how the creative teams that worked on Suspiria and The Chilling Adventures of Sabrina work with the body of the witch as well as how both cinematic pieces work with the trope of the Mother, the Maiden, and the Crone, an archetype popularized by Wiccan theology but also used in Celtic and Hellenic mythology, while simultaneously focusing on how the aforementioned theories work together to make the body and idea of the witch a patriarchal, theoretical, and socio-political nightmare. While both works stem from different cinematic and narrative traditions – one teen horror and the other art house – they both examine complex relationships between symbolic meaning and pre-linguistic, or semiotic, spaces.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.